Prevalence, Antibiotic Resistance And Molecular Characterization Of Aeromonas Spp., Salmonella Serovars And Listeria Spp. Isolated From Catfish (Clarias Gariepinus) And Tilapia (Tilapia Mossambica) Obtained From Wet Markets And Ponds - Budiati, Titik (2014)
This work reports on the prevalence, antibiotic resistance and molecular characterization of Aeromonas species, Salmonella serovars and Listeria species isolated from catfish (Clarias gariepinus) and tilapia (Tilapia mossambica) obtained from wet markets and ponds (earthen ponds and ex-mining pools) in Northern region of Malaysia. A total 163 of Aeromonas spp, 43 of Salmonella serovars, and 54 Listeria spp. was isolated from 32 catfish carcass rinse, 32 catfish intestines, 32 tilapia carcass rinse, 32 tilapia intestines and 44 water samples. Catfish, tilapia and water samples were obtained from nine wet markets and eight ponds in Penang, Kedah and Perak, Malaysia (2008 – 2009). Prevalence of Aeromonas spp., Salmonella serovars and Listeria spp. in catfish was 14/32 (43.8%), 9/32 (28.1%), and 10/32 (31.3%), respectively. Prevalence of Aeromonas spp., Salmonella serovars and Listeria spp. in tilapia was 21/32 (65.6%), 14/32 (43.8%), and 18/32 (56.3%), respectively. Aeromonas spp. was resistant to clindamycin, rifampin, and spectinomycin. Salmonella serovars were resistant to clindamycin, rifampin, and tetracycline. Listeria spp. was resistant to ceftazidime and clindamycin. The predominant antibiograms of A. hydrophila was AzmDaRdSh (6/62).